If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = 2(2x + -3) Reorder the terms: -6 + 5x = 2(2x + -3) Reorder the terms: -6 + 5x = 2(-3 + 2x) -6 + 5x = (-3 * 2 + 2x * 2) -6 + 5x = (-6 + 4x) Add '6' to each side of the equation. -6 + 6 + 5x = -6 + 6 + 4x Combine like terms: -6 + 6 = 0 0 + 5x = -6 + 6 + 4x 5x = -6 + 6 + 4x Combine like terms: -6 + 6 = 0 5x = 0 + 4x 5x = 4x Solving 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 1x = 4x + -4x Combine like terms: 4x + -4x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 2(2l+6)=28 | | t+38=3t+28 | | 5x+5=2x+15+x | | -5g+2.3=-18.1 | | 22x^5-44x^4+121x=0 | | 6x+19=2080 | | 17g+16=10 | | x^((5)/(4))=243 | | ×/3-5=3 | | 36/60= | | 12/7q-1/21q=q-4/3 | | x*(x+1)-2x+1=3x-3 | | 35h+25=40 | | N-20=-3(n-4) | | 10x=10-5x | | 6x-12x=-18 | | 9b+6b= | | 2t+18=3t+3 | | 10x-15=-5-5x | | 21=-3+6x | | 2x+2(.5x)=y | | 0.8x=20/x | | 0=3x^4+6x^3 | | 3x+9=-111 | | 11x^3*7x^7/3 | | 2x+2(.5x)=3 | | 1.25d=7.4 | | 3s=2s+17 | | 2(y+1)+-3(1-y)=3(y+2) | | k-2.5/5.2=-0.418 | | 6/21=x/42 | | 8/2y=7 |